2022
DOI: 10.3389/fimmu.2022.843452
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduced-Dose Anti-Human T-Lymphocyte Globulin on Overall and Donor-Specific T-Cell Repertoire Reconstitution in Sensitized Kidney Transplant Recipients

Abstract: BackgroundPre-sensitized kidney transplant recipients have a higher risk for rejection following kidney transplantation and therefore receive lymphodepletional induction therapy with anti-human T-lymphocyte globulin (ATLG) whereas non-sensitized patients are induced in many centers with basiliximab. The time course of lymphocyte reconstitution with regard to the overall and donor-reactive T-cell receptor (TCR) specificity remains elusive.Methods/DesignFive kidney transplant recipients receiving a 1.5-mg/kg ATL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The one available prospective study applying this technology to a standard renal transplant cohort is an excellent proof of feasibility and supports a potential role in monitoring alloreactivity but is inconclusive due to low enrollment and short-term follow-up ( 91 ). Studies on the effects of lymphodepletion on the T cell repertoire have been in consensus on an increase in donor-reactive CD4+ frequency; one study that investigated repertoire changes in rATG and Basiliximab induced patients found similar increases in alloreactive CD4+ but not CD8+ T cell frequency, supporting an earlier study that found patients receiving ATG showed post-depletional CD4+ CD25+ Treg and CD4+ effector memory phenotype ( 57 , 83 ). This emphasizes the importance of CD4+ T cells in the alloimmune response and the need to focus monitoring efforts on them.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The one available prospective study applying this technology to a standard renal transplant cohort is an excellent proof of feasibility and supports a potential role in monitoring alloreactivity but is inconclusive due to low enrollment and short-term follow-up ( 91 ). Studies on the effects of lymphodepletion on the T cell repertoire have been in consensus on an increase in donor-reactive CD4+ frequency; one study that investigated repertoire changes in rATG and Basiliximab induced patients found similar increases in alloreactive CD4+ but not CD8+ T cell frequency, supporting an earlier study that found patients receiving ATG showed post-depletional CD4+ CD25+ Treg and CD4+ effector memory phenotype ( 57 , 83 ). This emphasizes the importance of CD4+ T cells in the alloimmune response and the need to focus monitoring efforts on them.…”
Section: Discussionmentioning
confidence: 70%
“…MLC and TCR sequencing was performed at baseline and the alloreactive repertoire tracked for a year. They showed that over 1 year the percentage of peripheral CD4+ but not CD8+ donor-reactive T cells increased at similar frequencies across both groups ( 57 ). While these data do not shed further light on the diagnostic utility of TCR sequencing it suggests that there is no significant difference in T cell alloreactivity associated with either induction method alone.…”
Section: Resultsmentioning
confidence: 99%
“…We note that in the past we could not measure a drop in either CD4 + or CD8 + clonotype counts in transplant recipients receiving a reduced ATLG dose. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Our JSD estimates, which compared each post-transplant repertoire to the respective pre-transplant baseline, point to only minor turnover occurring in all our study subjects, especially in CD8 + populations. They approach those of transplant patients who received reduced-dose ATLG induction, 23 more so than those of irradiated CKBMT subjects. 18 Also unlike irradiated subjects, the case patients analyzed here showed only a minor reduction in the number of alloreactive clonotypes detectable in the circulating repertoire and were, in that respect, not clearly distinguishable from the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation